2023
DOI: 10.3389/fpls.2023.1154905
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability of tropical × temperate maize inducers for haploid induction rate, R1-nj seed set, and agronomic traits

Abstract: In vivo maternal haploid induction in isolation fields is proposed to bypass the workload and resource constraints existing in haploid induction nurseries. A better understanding of combining ability and gene action conditioning traits related to hybrid inducers is necessary to set the breeding strategy including to what extent parent-based hybrid prediction is feasible. This study aimed to evaluate the following in tropical savanna in the rainy and dry seasons for haploid induction rate (HIR), R1-nj seed set,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 67 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…Besides, reciprocal cross effects significantly impacted heterosis for yields; thus, superior sweet and waxy corn hybrids could be obtained when reciprocal crosses were included (Dermail et al 2018). In contrast, other similar studies using three gene pools of field corn (temperate inducers, tropical inducers, tropical noninducers) under different growing seasons concluded that reciprocal effects, including maternal and non-maternal were significant, but it could be negligible for anthesis date, silking date, plant height, ear height, yield components, and final seed set (Dermail et al 2023).…”
Section: Analysis Of Variance and The Minor Importance Of Reciprocal ...mentioning
confidence: 95%
See 2 more Smart Citations
“…Besides, reciprocal cross effects significantly impacted heterosis for yields; thus, superior sweet and waxy corn hybrids could be obtained when reciprocal crosses were included (Dermail et al 2018). In contrast, other similar studies using three gene pools of field corn (temperate inducers, tropical inducers, tropical noninducers) under different growing seasons concluded that reciprocal effects, including maternal and non-maternal were significant, but it could be negligible for anthesis date, silking date, plant height, ear height, yield components, and final seed set (Dermail et al 2023).…”
Section: Analysis Of Variance and The Minor Importance Of Reciprocal ...mentioning
confidence: 95%
“…Meanwhile, the two-way interaction between genotype and location in tropical rainforest Indonesia was important for flowering times, plant architecture, yield components, and grain yield in field corn (Azrai et al 2022). In tropical savanna Thailand, however, the common G × E variation for agronomic traits and yields in field corn and vegetable corn was two-way interaction between genotype and season (Dermail et al 2020;Fuengtee et al 2020;Dermail et al 2022;Ja et al 2022;Dermail et al 2023). Under a tropical savanna climate, the dry season was more suitable for corn growth and development to obtain a better seed set than the rainy season (Sintanaparadee et al 2022).…”
Section: Analysis Of Variance and The Minor Importance Of Reciprocal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Temperate maize stocks typically perform poorly under tropical/sub-tropical conditions and are often difficult to maintain and use. For example, temperate haploid inducers exhibit short stature, poor pollen production and seed set and susceptibility to diseases when grown in the tropics (Dermail et al, 2023;Prasanna, 2012;Prigge, Schipprack, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Temperate maize stocks typically perform poorly under tropical/sub‐tropical conditions and are often difficult to maintain and use. For example, temperate haploid inducers exhibit short stature, poor pollen production and seed set and susceptibility to diseases when grown in the tropics (Dermail et al, 2023; Prasanna, 2012; Prigge, Schipprack, et al, 2012). These constraints have been overcome with the development of first‐generation tropically adapted inducer lines (TAILs) and second‐generation inducer lines (CIM2GTAILs), which have better agronomic performance compared to temperature inducers (CIMMYT, 2017).…”
Section: Introductionmentioning
confidence: 99%